Structure–property relationships of antibacterial amphiphilic polymers derived from 2-aminoethyl acrylate. Issue 115 (5th November 2015) - Punia, Ashish; Debata, Priya R.; Banerjee, Probal; Yang, Nan-Loh
Abstract : The effects of variation in the topographical position of the cationic center and hydrophobic segments on the antibacterial and hemolytic activities of polyacrylates. Abstract : The findings from the investigation of an ensemble of amphiphilic polymers derived from 2-aminoethyl acrylate establish significant effects of variation in the topographical position of the cationic center and hydrophobic segments on their biological activities. For example, the isomeric polymer pair of poly(6-aminohexylacrylate) and poly(2-(butylamino)ethyl acrylate) show striking differences in their biological activities, with the former having biological activities orders of magnitude higher. The trend of the activities of alkyl tails attached to the charge center shows an abrupt increase in biological activity at butyl length in the series of methyl to butyl tail. The distribution and interaction of the charge center in the chain domain is one of the main parameters in influencing polymer activities. Within the 2-aminoethyl acrylate system of homo- and copolymer, the homopolymer has its cationic centers closely distributed along the amphiphilic macromolecular chain with proximity to the backbone leading to rigid conformations not conducive to the attachment of the polymer to the cell surface. In copolymers, the incorporation of uncharged counits increases the distance between the cationic centers, resulting in significant reduction of charge repulsion and thus enhancing the flexibility of the chain conformation. This is conducive for polymer-cell association, leading to a remarkable surge in orders of magnitude of biological activity but with low selectivity against bacteria over red blood cells.